Korporasi Dalam Hukum Organisasi Bisnis Islam - Afdal, Windi (Jurnal Hukum & Pembangunan, 2016)
This article critically examine the reason of the delay in introducing Islamic law into the form of corporate business to help Muslim society in their economic activity. In addition, this study also aims to provide an explanation regarding the legal validity of the concept of corporate legal personality in Islamic law. This study aplied the method of juridical-normative research by using socio-legal analysis. The article conclude that: (1) Delayed development of corporate business organizations in the Muslim world caused by; the view that organizing community by using corporate form can damage the vision of united ummah because it can lead to factionalization in the community; The lack of capital resources because it endowment institution on wakaf; stagnant institutional development of business organizations in Islamic law; and last the capital group of Merchant class could not consolidated because hard for them to keep persistence on capital accumulation for accross generations and for conglomeration activity. (2) Fuqoha actually understand the concept of personality legal and it aplicable to non-humans corpus, but they are reluctant to develop this concept because it can’t work the legal system that they have created. Therefore, the formation of a nonhuman corpus actually possible in Islam by rule rely on assiyasah syariyah as the ulil domain domain (political authority).